L’usure et la défiguration chez Dickens - Marie-Amélie Coste (Cahiers Victoriens et Edouardiens)
Dickens, like Proust, puzzles over the question of the permanence of one’s being in time, beyond the changes to which it is subjected. He looks for the seat of the subject, and wonders what is the essential part of a human being. But essence is both well defined and pre-defined: existing first potentially, it then does not seem to be able to live up to its promises.It appears first in the characters’ ageing, which is rarely seen as a natural process, but rather as a rapid movement towards physical degradation and wearing out.However, this gradual deterioration of the characters can be brutally stopped by the advent of a trauma. Although traumas cause sudden and premature ageing, often shown in the characters’ disfiguring, it also has beneficial effects. Indeed, the inner tremor produced by the physical shock enables the characters to evolve morally. But traumas also present themselves as a temporary death, allowing Dickens to explore this strange dissociation between body and mind. Being a reversible state, traumas allow characters to give witness to the ebb and flow of life. Dickens’s intense interest in those states of shock underlines his impossible desire to comprehend the passage from life to death.Death is defined as the point just beyond knowledge. Corpses are the enigmatic signs of it, not giving any clue to what has become of the being. This insolvable mystery pushes Dickens to explore near-death cases, as if better to approach death itself.